PERAN ORGANISASI NON-PEMERINTAH (NGO) DALAM MENANGANI PENCARI SUAKA DI INDONESIA - Seftina Kuswardini; Ulul Azmiati Auliyah (Dauliyah: Journal of Islam and International Affairs, 2021)
The existence of refugees in Indonesia in the past decade is gradually increasing. Some countries such as  Afghanistan,  Myanmar,  Sudan,  Sri Lanka, Somalia and Ethiopia make Indonesia as one of the transit areas as well as a destination for those who come out of their country to look for another place to live due to the ongoing conflict and war. But unfortunately Indonesia does not have the right and authority to accept asylum seekers because it is not yet a state party which ratified the 1976 refugee Protocol and the 1951. Convention. However, the government continues to provide assistance on a humanitarian basis. UHNCR and IOM became the first organizations to address the existence of refugees  in Indonesia. Both are government organizations that have the authority to regulate the existence of asylum seekers in various countries. Given this, it is necessary to know the existence and role of non-governmental organizations in overcoming the existence of refugees in Indonesia. This study uses a qualitative descriptive method where data is obtained through observation and interviews with one non-governmental organization. This research results in an internationally accredited journal publication and will contribute to academics in the social humanities field.